2020
DOI: 10.1186/s12872-020-01628-5
|View full text |Cite
|
Sign up to set email alerts
|

Cultural adoption, and validation of the Persian version of the coronary artery disease education questionnaire (CADE-Q): a second-order confirmatory factor analysis

Abstract: Background: Evaluating knowledge in patients with coronary artery disease requires a specific measure. The aim of the present study was to translate and evaluate the CADE-Q in patients with coronary artery disease in Iran. Methods: Forward-backward procedure was applied to translate the questionnaire from English into Persian. Then a cross-sectional study was conducted to evaluate psychometric properties of the questionnaire. A sample of patients with coronary artery disease attending to cardiac departments of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 34 publications
(37 reference statements)
1
10
0
2
Order By: Relevance
“…The analysis of criterion validity was based on a previous study [26], with higher knowledge about the disease associated with higher educational level. These results are consistent with previous studies [16,24,27], as well as the validation of the other 3 versions of CADE-Q II [16,24,25]. Although weak, the correlation between "self-care confidence" scale of the SC-CHDI and CADE-Q II scores aligns with previous studies that report that knowledge can be associated with better behaviors 2 .…”
Section: Discussionsupporting
confidence: 91%
“…The analysis of criterion validity was based on a previous study [26], with higher knowledge about the disease associated with higher educational level. These results are consistent with previous studies [16,24,27], as well as the validation of the other 3 versions of CADE-Q II [16,24,25]. Although weak, the correlation between "self-care confidence" scale of the SC-CHDI and CADE-Q II scores aligns with previous studies that report that knowledge can be associated with better behaviors 2 .…”
Section: Discussionsupporting
confidence: 91%
“…The number of tool items and factors of involved studies were different. The maximum item number was 60 (De Melo Ghisi, Grace et al, 2013), the minimum number of dimensions were three (Marofi et al, 2020) and the maximum number was 11 dimensions in one study (Phelan et al, 1989).…”
Section: Quality Evaluation Of the Studiesmentioning
confidence: 99%
“…All studies were peer-review original articles. Majority of the studies (n=5) were showed in the Canada (De Melo Ghisi et al, 2016;De Melo Ghisi et al, 2015;De Melo Ghisi, Grace et al, 2013;De Melo Ghisi & Oh, 2021; followed by Iran (n=2) (Marofi et al, 2020;Sayadi et al, 2021), Brazil (n=4) (De Melo Ghisi et al, 2010;De Melo Ghisi et al, 2018;De Melo Ghisi et al, 2014Santos et al, 2019 , China (n=1) (Chen et al 2018), Australia (n=1) (Smith et al, 2015), Netherlands (n=1) (Van Engen-Verheul et al, 2012) and USA (n=1) (Phelan et al, 1989).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations